Strategic Management / Concepts and Cases: Tenth Edition - Strickland A.J; Thompson Arthur (Irwin Mcgraw-Hill, 1998)
The Concepts and Techniques of Strategic Management, The Strategic Management Process: An Overview, The Three Strategy-Making Tasks: Developing a Strategic Vision and Setting Objectives and Crafting a Strategy, Industry and Competitive Analysis, Evaluating Company Resources and Competitive Capabilities, Strategy and Competitive Advantage, Matching Strategy to a Company's Situation, Strategy and Competitive Advantage in Diversified Companies, Evaluating the Strategies of Diversified Companies, Implementing Strategy: Building Resource Capabilities and Structuring the Organization, Implementing Strategy: Budgets and Policies and Best Practices and Support Systems and Rewards, Implementing Strategy: Culture and Leadership, Cases in Strategic Management, A Guide to Case Analysis, Index.
The Concepts and Techniques of Strategic Management, The Strategic Management Process: An Overview, The Three Strategy-Making Tasks: Developing a Strategic Vision and Setting Objectives and Crafting a Strategy, Industry and Competitive Analysis, Evaluating Company Resources and Competitive Capabilities, Strategy and Competitive Advantage, Matching Strategy to a Company's Situation, Strategy and Competitive Advantage in Diversified Companies, Evaluating the Strategies of Diversified Companies, Implementing Strategy: Building Resource Capabilities and Structuring the Organization, Implementing Strategy: Budgets and Policies and Best Practices and Support Systems and Rewards, Implementing Strategy: Culture and Leadership, Cases in Strategic Management, A Guide to Case Analysis, Index.